DEVELOPMENT OF ONLINE-BASED TWO STAY TWO STRAY LEARNING METHODS TO IMPROVE STUDENT LEARNING ACHIEVEMENT AND MOTIVATION - Agung Panji Sasmito; Febriana Santi Wahyuni; Hani Zulfia Zahro' (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2023)
Since the Covid-19 outbreak, the learning implementation has shifted from offline to online. This transition causes students to have difficulty participating in learning, especially actively participating in the online learning process. One of the causes of this is the low learning motivation of students, teachers lack innovation in online learning methods. The objective of this study is to develop an alternative online learning method during the Covid-19 outbreak in the form of the online-based Two Stay Two Stray method. This is a Research and Development using the ADDIE model. The results show that the validity of the lesson plan is at an average value of 3.54, while the validity of the learning model in the expert validation and pilot tests is at an average value of 3.46 and 3.14. The results of the research show that the empirically developed method has proven to be an effective and valid learning method that enhances student comprehension and motivation.